The Effect Of Understanding Tax Digitalization, Digital Literacy On Tax Awereness - Siagian, Vienzo; Hutabarat, Francis; Siagian, Harlyn (Universitas Ibn Khladun Bogor, 2024)
Taxpayer awareness involves understanding, accepting, and complying with tax regulations while demonstrating a willingness to fulfill tax obligations. This research aims to examine the impact of digital literacy on tax education among residents of West Bandung. Using the Slovin formula, 100 respondents were selected through probability sampling with a random technique. Data analysis was carried out using partial least squares and descriptive statistical methods. The findings of the study reveal that digital literacy and the digitalization of tax processes significantly and positively influence taxpayer awareness in the West Bandung area. These results highlight the importance of integrating digital tools into tax education programs, as they enhance taxpayers' knowledge and compliance with tax regulations. This research underscores how improved digital literacy can lead to a better tax compliance, providing valuable insights for policymakers. It suggests that by embracing digitalization, local communities can foster greater awareness and understanding of their tax responsibilities.